2017
DOI: 10.29311/mas.v15i1.658
|View full text |Cite
|
Sign up to set email alerts
|

The job that no one wants to do? Museum educators’ articulations about guided tours

Abstract: The aim of this paper is to investigate museum educators' articulations of their performance during guided tours. The paper investigates preparations for a guided tour, considerations related to doing guided tours and the events after the guided tour. The text focus especially on preparation and the aftermath as this is not normally discussed in research on museum education. The paper is based on participant observation of guided tours, filming of guided tours and qualitative semi-structured interviews. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…In many science centres and museums there is a long tradition of women occupying educational positions and the disinterest in the work could be situated within a hierarchal gender order, where attitudes to gender also affect attitudes to work carried out by women. This, I propose, has resulted in that educators within (science centres and) museums are considered, by themselves and others, as having a low status and that the work that they are doing is not seen as a true job (Rodéhn 2017). This reality, of course, stands in stark contrast to the rhetoric in Critical Museum and Heritage Studies that positions education as the most important task that museum and science centres have (see Rodéhn 2017 for a discussion).…”
Section: The Educatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In many science centres and museums there is a long tradition of women occupying educational positions and the disinterest in the work could be situated within a hierarchal gender order, where attitudes to gender also affect attitudes to work carried out by women. This, I propose, has resulted in that educators within (science centres and) museums are considered, by themselves and others, as having a low status and that the work that they are doing is not seen as a true job (Rodéhn 2017). This reality, of course, stands in stark contrast to the rhetoric in Critical Museum and Heritage Studies that positions education as the most important task that museum and science centres have (see Rodéhn 2017 for a discussion).…”
Section: The Educatorsmentioning
confidence: 99%
“…Although educators have a long history in science centres and museums there has been limited recognition and understanding of their work (Tran and King 2007). Many educators are employed on a temporary basis or payed by the hour, and the job is often seen as a stepping stone to another museum position (Rodéhn 2017). I would even go as far as argue that this is a question of gender.…”
Section: The Educatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, further research is needed to clarify current training practices and their effects on guiding practice/performance. The scoping review revealed that guided tours are unique and complex events (Grenier, 2009(Grenier, , 2011Martinello & Cook, 1983;Rodehn, 2017;Tran & King, 2009) and that docents require a range of skills and competencies (e.g., Schep et al, 2018a) and adequate training (e.g., Grenier, 2011;Oleniczak, 2016). However, the adequacy of current docent training approaches is questionable (e.g., Bevan & Xanthoudaki, 2008;Castle, 2006;DePrizio, 2016;Grenier, 2008;Tran, 2008b).…”
Section: Implication For Researchmentioning
confidence: 99%
“…Biophilia foregrounds empowering change agent qualities for museum educators such as being proactive with small specifics to improve a situation (Hirsch 2000). However, the limited recognition and understanding of their work, both in research and practice (Tran and King 2007), leaves museum educator's profession periodically in a state of uncertainty, low status and vulnerability (Reeve and Woollard 2015;Roberts 1997;Rodéhn 2017;Vallance 2007). Education is inevitably political, especially in relation to critical, place-based and progressive pedagogy (Gruenewald 2003;Hein 2012).…”
Section: Biophilia's 'Infectious' Pedagogical Approach and The Potentmentioning
confidence: 99%